Anatomy behind the Paramedian Platysmal Band: A Combined Cadaveric and Computed Tomographic Study. (16th September 2021) - Davidovic, Kristina; Frank, Konstantin; Schenck, Thilo L.; Cohen, Steven R.; Dayan, Steven; Gotkin, Robert H.; Sykes, Jonathan M.; Liew, Steven; Gavril, Diana; Cotofana, Sebastian
Abstract : Background: The muscular hypothesis explanation of the pathophysiology behind paramedian platysmal bands does not seem to provide a sufficient explanation for the clinical presentation of these platysmal bands in aged individuals with cervical soft-tissue laxity. The purpose of this study was to investigate the fascial relationships of the anterior neck to enhance appropriate surgical treatment. Methods: Retrospective analysis of computed tomographic scans of 50 Caucasian individuals (mean age, 55.84 ± 17.5 years) and anatomical dissections of 20 Caucasian and 10 Asian body donors (mean age, 75.88 ± 10.6 years) were conducted. Fascial adhesions were classified according to platysma fusion types, and platysma mobility was tested during dissection procedures. Results: Fusion between the left and right platysma muscles occurred in 64 percent in the suprahyoid region and in 20 percent at the thyroid cartilage, and in 16 percent, the platysma attached to the mandible without fusion. In the absence of muscular fibers, a fascial adhesion zone with limited mobility was observed where the superficial cervical fascia fused with the investing layer of the deep cervical fascia. Conclusions: Muscular contraction of the platysma results in elevation of the most medial platysma muscle fibers, which are not attached in the fascial adhesion zone. The presence of a fatty layer deep to the platysma enables platysmal movement and anterior and inferior gliding of the skin and platysma when cervical soft-tissue laxity exists. Surgical treatments should include transection of the fascial adhesion; this could potentially prevent the recurrence of paramedian platysmal bands.